Transparency and Public Value—Analyzing the Transparency Practices and Value Creation of Public Utilities. Issue 12 (14th October 2016) - Douglas, Scott; Meijer, Albert
ABSTRACT: This article examines to what extent transparency is a condition for the creation of public value. Transparency is usually narrowly defined as a tool for external stakeholders to monitor the internal workings of an organization, but public value management positions transparency as a broader instrument for actively engaging stakeholders. We investigate empirically whether transparency is indeed necessary to create public value, distinguishing between transparency about operational capacity, authorizing environment, and value proposition. We find that more transparent public organizations achieved higher public value scores, especially if they disclosed information about the design and dynamics of their authorizing environment.